“La grafo plástica como estrategia en la estructuración del esquema corporal en los niños de preparatoria” - Chicaiza Tigasi, Leidy Mishelle (2023)
Grapho-plastic art is essential in the teaching-learning process, as it is a method for developing children's reading and writing skills and the integral stimulation of their creative and expressive imagination. The objective of this work was to diagnose the use of grapho-plastic art in the development of the structuring of the body schema in high school children in the parish of Guangaje in the canton of Pujilí, province of Cotopaxi, using a qualitative methodology with a descriptive approach and field application; we used interviews with teachers and observation sheets for the children in initial education, taking into account eleven different institutions within the parish. The main results indicate a deficit in the correct application of these techniques in the classroom processes and, therefore, limited children's psychomotor skills. In conclusion, it is necessary to intervene at the management and planning level to improve the teaching-learning processes.